11. The Isolation And Identification Of Bacteria Salmonella Sp On Quail Egg Shell In Traditional Markets Ulee Kareng Banda Aceh - Erina Erina; Azmansyah Azmansyah; Darniati Darniati; Fakhrurrazi Fakhrurrazi; Safika Safika; Tongku N Siregar (Jurnal Medika Veterinaria, 2019)
This research aim was to determine the level of bacterial contamination of Salmonella sp on quail egg. The samples used in this research was 24 shell of quail eggs obtained from eight stores in traditional markets in Ulee Kareung Banda Aceh. The shell was crushed with a mortar and then cultured on SCB media (selenite cysteine broth). Isolation and identification was conducted by using SSA media culture, Gram staining, and biochemical tests. The results of this research showed that the shell of quail eggs contained Salmonella sp. Therefore it can be concluded that the quail eggs sold in Ulee Kareung traditional market were contaminated by Salmonella sp.